Narratives of immigrant Muslim women in Fordsburg - Moodley, Kavishka (My University, 2019)
The narratives of immigrant Muslim women in Fordsburg are depicted through multiple lenses in this study. The research was primarily focused on exploring the sense of belonging that this subaltern community felt whilst residing and working in Fordsburg. Fordsburg is constituted of a unique historical, political, economic, social and cultural background which immigrant Muslim women constantly navigate within. The intersectionality of these constructs provides a unique sense of place upon which they can shape their identities. This report sets to explore the narratives that immigrant Muslim women tell within the space of Fordsburg. These narratives engage with various themes around sense of belonging, reading silence in narratives, feminism, xenophobia and exploitation. Based on these narratives, the study seeks to determine how immigrant Muslim women narrate the experience of the space of Fordsburg in relation to their home country. Methods of accessing this subaltern narrative were explored including the manner in which reading of silences was analysed as an alternative and important form of communication. It also analyses how these women gain a sense of self which is related to sense of place and how it plays out in terms of sense of belonging. Lastly, it explores the interface of the researcher in working with the subaltern community. Findings suggest that sense of place is intimately linked to sense of belonging, which is integral in determining one’s sense of self. The narratives are found to be a method in which the subaltern community can be heard and is able to speak.
minor dissertation submitted in partial fulfillment of the requirements for the award of the degree of Masters of Arts in Community-based Counselling Psychology Faculty of Humanities University of the Witwatersrand 2018
Keywords: Muslim women--South Africa--Social conditions.; Women immigrants--South Africa